Analisis Buku Siswa “Sejarah Kebudayaan Islam” Kelas VII Madrasah Tsanawiyah Kurikulum 2013 - Irinne Fauz Yusria (LP2M STIT Palapa Nusantara, 2020)
In the implementation of Curriculum 2013, a book teaching or book student can be used as a source of learning. Books students are prepared to facilitate the participant students in understanding the material that is delivered and becomes the handle of students in the process of learning. The research is aimed to find out the things what only the must be considered in analyzing a book, so the reader can determine the model of books students like that worthy used both in the perspective of education as well as the perspective of psychology. The analysis of the book is, the expected party who is concerned can make this as a matter of evaluation for publication the next. The method that is used in research this is a library research or research literature. The data obtained is of a source of primary, among other books students History of Culture Islam MTs Class VII, thesis, theses, and reports of research. While the source of the secondary are journals, articles, textbooks, and sources other related. The results of the research of this is there are several aspects that must be considered in analyzing the book, among others relevance with the curriculum, the clarity of the concept, the content of the material, illustration, aspects of language, ibrah, as well as the time allocation. From the contents are, there is some content that can be connected with the theory of psychology. The books of Islamic Culture History VII grade students with 2013 Curriculum are as follows: 1) Relevance with the curriculum, KI and KD compiled are relevant to the 2013 curriculum because they are in accordance with Permenag No. 912 in 2013, 2) The clarity of the concept of the book SKI MTs Class VII Curriculum 2013 is already quite clear and easy to understand by presenting a map of concepts in every beginning of the chapter, 3) Fill material if in terms of in terms of psychology, the depth and breadth of the material is already in accordance with age participants learners, 4) illustrations, for the presentation of illustrations if the review of the terms of the psychology still less precise in the placement and still there are some images that are less appropriate to the theme, such as cover, 5) Aspects of linguistic, the language that is used in the book is pretty straightforward, effective, communicative, dialogical and interactive, 6) ibrah in the book of this can be seen in the column